Creative Activities and Collaboration on Web 2.0: Towards a New Typology of Prosumption - Žilinskaitė, Rima (Sociologija. Mintis ir veiksmas, 2021)
The concept of prosumption is commonly used to identify and analyse the specificities of activities on Web 2.0. This article provides the minimal and maximal definition of the concept by decomposing available conceptualisations. Including maximal number of mutually consistent attributes, it amounts to the definition of the ideal type of prosumption. The paper critically assesses the existing classifications of prosumption, and proposes a new, more systematic typology. It is designed on the basis of three conceptual dimensions: 1) the nature of the prosumptive activities in collaborative terms (individual/collaborative); 2) the primary reason for engaging in a prosumptive activity (prosumption in order to create/prosumption in order to use); 3) the level of training required from the prosumer (conditionally divided into “specialist” and “amateur”). The eight types formulated cover essentially the whole spectrum of prosumptive activities and direct to the more detailed empirical studies of motivations and intensity of engagement in prosumption.